Muscular Pre-activation Can Boost the Maximal Explosive Eccentric Adaptive Force - Schaefer, Laura V.; Bittmann, Frank N. (Frontiers in Physiology, 2019)
Abstract The improvement of power is an objective in training of athletes. In order to detect effective methods of exercise, basic research is required regarding the mechanisms of muscular activity. The purpose of this study is to investigate, whether or not a muscular pre-activation prior to an external impulse-like force impact has an effect on the maximal explosive eccentric Adaptive Force (xpAFeccmax). This power capability combines different probably power enhancing mechanisms. To measure the xpAFeccmax an innovative pneumatic device was used. During measuring the subject tries to hold an isometric position as long as possible. In the moment in which the subjects´ maximal isometric holding strength is exceeded, it merges into eccentric muscle action. This process is very close to motions in sports, where an adaptation of the neuromuscular system is required, e.g. force impacts caused by uneven surfaces during skiing. For investigating the effect of pre-activation on the xpAFeccmax of the quadriceps femoris muscle, n=20 subjects had to pass three different pre-activation levels in a randomized order (level 1: 0.4 bar, level 2: 0.8 bar, level 3: 1.2 bar). After adjusting the standardized pre-pressure by pushing against the interface, an impulse-like load impacted on the distal tibia of the subject. During this, the maximal explosive eccentric Adaptive Force was detected. The isometric MVC was also measured. The torque values of the xpAFeccmax were compared with regard to the pre-activation levels. The results show a significant positive relation between the pre-activation of the quadriceps femoris muscle and the xpAFeccmax (male: p=.000, η²=683; female: p=.000, η²=907). The average percentage increase of torque amounted +28.15 ± 25.4% between MVC and xpAFeccmax with pre-pressure level 1, +12.09 ± 7.9% for the xpAFeccmax comparing pre-pressure levels 1 vs. 2 and +2.98 ± 4.2% comparing levels 2 and 3. A higher but not maximal muscular activation prior to a fast impacting eccentric load seems to produce acutely a higher force outcome. Different possible physiological explanatory approaches and the use as a potential training method are discussed.